Sing a song of popcorn : every child's book of poems - Brown, Marcia; De Regniers, Beatrice Schenk (New York : Scholastic Inc., 1988)
A collection of 115 poems by a variety of well-known authors with illustrations by nine Caldecott medalists.
Rev. ed. of: Poems children will sit still for. 1969.
Includes indexes.
Keywords: Children's poetry; American poetry -- Collections; English poetry -- Collections